Association between dietary habits and incident thyroid cancer: A prospective cohort study - Nguyen, Linh Thi Dieu; Gunathilake, Madhawa; Lee, Jeonghee; Kim, Jeongseon (Frontiers in Nutrition, 2023)
Background: In addition to the thyroid cancer (TC) risk from lifestyle and environmental factors such as radiation exposure, some studies have indicated that diet may affect TC development; however, previous findings are inconsistent. The objective of our study was to investigate the association between dietary habits and TC risk in a Korean population. Methods: A total of 13,973 participants were selected after excluding ineligible subjects from the Cancer Screenee Cohort at National Cancer Center in Korea from October 2007 to December 2021. Participants were followed until May 2022 to identify incident TC cases. Information on dietary habits and general characteristics was collected using a self-report questionnaire administered at enrollment without keeping track of changes in eating habits during the follow-up period. A Cox proportional hazards model was used to determine the hazard ratio (HR) and 95% confidence interval (CI) of TC risk for each dietary factor. Results: A total of 138 incident TC cases were identified during the median follow-up period of 7.6 years. Of the 12 dietary habits evaluated, only two habits showed significant associations with TC. A significantly decreased TC risk was found among participants who consumed milk and/or dairy products 5 or more days a week (adjusted HR (aHR), 0.58; 95% CI, 0.39-0.85). Notably, a stronger protective effect of dairy consumption was observed in participants aged ≥ 50 years (aHR, 0.44; 95% CI, 0.26-0.75), in women (aHR, 0.53; 95% CI, 0.35-0.81), and in nonsmokers (aHR, 0.60; 95% CI, 0.39-0.92). There was a reduced risk of TC in participants with meal durations longer than 10 minutes (aHR, 0.58; 95% CI, 0.41-0.83). However, this association was limited to individuals aged ≥ 50 years (aHR, 0.49; 95% CI, 0.31-0.79), women (aHR, 0.61; 95% CI, 0.41-0.90), and nonsmokers (aHR, 0.62; 95% CI, 0.41-0.92). Conclusion: Our findings suggest that consuming milk and/or dairy products 5 or more days a week and having a meal duration longer than 10 minutes could be protective factors against TC, especially in individuals aged ≥ 50 years, women and nonsmokers. Further prospective studies are needed to investigate the association of dietary intake with specific types of TC.